Sistem Dashboard Segmentasi Pasar menggunakan Metode Customer Portfolio Management - nina fadilah najwa; mutia sari zulvi; Yohana Dewi Lulu (Jurnal Sosioteknologi, 2023)
Business competition is getting tighter, so MSMEs use influencer marketing as a marketing strategy for their products or services. The BrandQ application is an idea designed as an influencer marketing platform to connect MSMEs and influencers. BrandQ has a solution that can make it easier for MSMEs to find the right influencer based on product or service category, target market, and demographics. In developing the BrandQ application, a customer relationship management strategy is needed using the Customer Portfolio Management (CPM) method to analyze the right target market to obtain business opportunities and anticipate the risk of business failure. The output of the CPM analysis results is the system developer’s intuitive analysis and the data analysis in the form of a market segmentation dashboard system. The system was built using data mining and the K-Means algorithm to segment the market. Based on the black box testing results, the results show that the system has been 100% successful.